Robert Ludlum's the Treadstone exile - Hood, Joshua (The Treadstone series, 2021)
"Former Treadstone Operative Adam Hayes finds himself at the center of a web of warring factions and high-level secrets in the second novel in the Treadstone series, the newest addition to the Robert Ludlum universe"--